Kebermaknaan Hidup pada Caregiver yang Merawat Pasien Gangguan Jiwa - Alia Nanda Rumekti; FX Wahyu Widiantoro; Sapta Kurniawati (LPPM Universitas Proklamasi 45, 2023)
This research is a qualitative research. Data collection was carried out using observation and interview methods. This study aims to find out the positive energy that caregivers who care for patients with mental disorders should have as a counterweight to their negative emotions, to know the meaning of the meaningfulness of life, to know the sources of meaningfulness in life can be found, to know the importance of the meaningfulness of life owned by caregivers who care for patients with mental disorders, to know the caregiver's description who treat mental patients who have a meaningful life, knowing the meaningfulness of life can influence the attitudes and behavior of caregivers who care for mental patients in carrying out their daily lives and work responsibilities. Positive energy that can control and influence the caregiver's thoughts, feelings, and behavior is needed to balance negative emotions in the form of stress. The positive energy control needed is gratitude for life because in difficult or unpleasant conditions you still have luck behind it. The research subjects were caregivers who cared for mental patients at Pondok Tetirah Dzikir, Yogyakarta. Caregivers who have meaning in life have clear guidelines and goals in living their lives. Caregivers who have a meaning in life will feel that they have a useful, valuable, and meaningful life. As for caregivers who have no meaning in life, will feel boredom, emptiness, and meaningless life.